Dlx Genes, Neurogenesis and Regeneration in the Adult Zebrafish Brain - Weinschutz Mendes, Hellen (Université d'Ottawa / University of Ottawa, 2020)
The Dlx homeobox genes encode homeodomain transcription factors that are involved in multiple developmental aspects. In the brain, these genes take part in neuronal migration and differentiation, more precisely in the migration and differentiation of GABAergic neurons. Dysfunctions in the GABAergic system can lead to various pathological conditions, where impaired inhibitory function is one of the main causes of several neuropathies characterized by neuronal hyperexcitability. The Dlx genes are organized as bi-gene clusters and highly conserved cis-regulatory elements have been previously characterized to be fundamental for the regulation of Dlx expression in developing embryos of different vertebrates. The activity of these regulatory elements and the Dlx genes has been well studied in developmental stages of mice and zebrafish, but little is known about their activity in the adult brain. The extensive neurogenesis that takes place in the adult zebrafish brain provides an ideal platform for the visualization of mechanisms involving dlx genes during adulthood and their possible involvement in adult neurogenesis. Here we show novel information concerning the expression of dlx1a, dlx2a, dlx5a and dlx6a in the adult zebrafish brain and provide insight into the identity of cells that express dlx. We also demonstrate the involvement of dlx genes in brain regeneration and through lineage tracing, their fate determination in the adult zebrafish brain. Analyses in the adult zebrafish has revealed that all four dlx paralogs are expressed in the forebrain and midbrain throughout adulthood and expression is found in almost all areas presenting continuous proliferation. Most dlx-expressing cells present GABAergic neuronal identity in the adult forebrain where, in some areas they were identified as the Calbindin subtype. In some areas of the midbrain, especially within the hypothalamus, many dlxexpressing cell co-localized with a marker for neural stem cells. However, cells expressing dlx iii genes did not co-localize with markers for proliferating cells or for glia. Investigations during brain regeneration in response to injury in the adult zebrafish brain has revealed that dlx5a expression decreases shortly after lesion and that the dlx5a/6a bi-gene cluster, more specifically, dlx5a, is up regulated during the peak of regeneration response proposing a possible role for dlx during regeneration in adults. Studies of lineage tracing have shown the progeny of dlx1a/2a-expressing cells in adults are located within small clusters in different areas of the adult brain where they seem to become mature neurons. Our observations provide a better understanding about the role of dlx genes during adulthood, further contributing to the general knowledge of the molecular pathways involved in adult neurogenesis and regeneration in the zebrafish adult brain.
Keywords: dlx; neurogenesis; zebrafish; transcription factor; adult brain; lineage tracing